Mental health interventions in public health emergencies: The best and the rest in research, evidence, intervention, and policy responses - Sharon Abramowitz; Emma Louise Backe; Wilfred Gwaikolo; Susan Nkengasong; Dhruvi Banerjee; Sarah M. Murray (SSM - Mental Health)
Background: The COVID-19 pandemic showed the significant impact of epidemics on mental health and illustrated gaps in public health and epidemic response systems’ ability to respond to mental health and psychosocial needs. Objective: This study sought to identify the most and least helpful mental health and psychosocial support (MHPSS) strategies and elements for intervention in epidemics. Methods: An online survey with open ended questions was circulated via professional networks and listservs and completed by 11 MHPSS experts with experience in epidemics in July–August 2023. Data were analyzed using a thematic coding approach. Three case studies of MHPSS interventions from Liberia, South Africa, and Uganda are provided. Key findings: The most helpful MHPSS strategies were seen as community-based, integrated with other response systems, inclusive of vulnerable populations, drawing on lived experience and peer support, timely, and rapid. Unhelpful strategies rely on unnuanced sensitization messages, are siloed, and lack community consultation. Case studies illustrate the complexities of delivery in context and highlight the importance of lived experience, community engagement, and local adaptation for success. Discussion: MHPSS services can be employed nimbly and help respond to misinformation and disinformation but work best when integrated with other services. Capacity, particularly among community health workers, for these services must be elevated as a priority in emergency preparedness. While remote interventions are important, they cannot always reach those in most need, and social connection matters. These considerations can guide recognition of mental health as an interconnected public health priority in epidemic response going forward.